EKSISTENSI KESENIAN MUSIK TANJIDOR PADA PROSES PERNIKAHAN DI DESA SERUMPUN KABUPATEN SAMBAS - Syarifah Yesi Pramita Sari; Agus Sastrawan Noor; Astrini Eka Putri (Universitas Tanjungpura, 2020)
AbstractThis research is intended to describe the existence of musikal pleasure Tanjidor in the process of marriying Malays in the villge of Serumpun Sambas district this reseaarch USES qualitative methods with A descriptive- ethnographic approach with technique for data gathering that used are observation, interview and documentation. The data- collection tool that is observation guides, interview manuals, field notes and documentaries. The anal probing of data used is pre-d analysis, core analysis and cultural theme analysis testing data validity using extensions of observation, increased persistence and triangulation made up of source triangulation, triangulation of technique and time-triangulation based on research done on the Tanjidor music of the process of performing in weddiing tradisions, a processions of deconstructed processions still accompanied by Tanjidor music that has now grown considerably in growth wedding trditions taking place in the villing of umbas district. Because of some of the factors of the vavais, both internal and external factors, caused by socied by society both the send and the age.Keywords: Existence, Tanjidor Musical Art, Serumpun